Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/09583150802100197
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EuropeanPeristenus digoneutisloan in mirid populations in southern Ontario

Abstract: Lygus spp. Hahn (Hemiptera: Miridae) are serious pests of a wide variety of economically important crops in North America. A European parasitoid, Peristenus digoneutis Loan (Hymenoptera: Braconidae), released in the northeastern USA for the biological control of Lygus, has successfully established in nine states and in eastern Canada, including southeastern Ontario, southern Quebec and Nova Scotia. To determine the extent to which P. digoneutis has dispersed and established in mirid populations in Ontario, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…The phenology of P. digoneutis in North America predicted by our model is very similar to the observed phenology in south‐western Ontario, where P. digoneutis is now well established (Goulet & Mason, 2006; Gariepy et al , 2008). Nymphs parasitized by P. digoneutis were first found in the first and second week of June and then again from the third week of July to the end of August of two subsequent years (2007, 2008) (Mason et al , 2009).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The phenology of P. digoneutis in North America predicted by our model is very similar to the observed phenology in south‐western Ontario, where P. digoneutis is now well established (Goulet & Mason, 2006; Gariepy et al , 2008). Nymphs parasitized by P. digoneutis were first found in the first and second week of June and then again from the third week of July to the end of August of two subsequent years (2007, 2008) (Mason et al , 2009).…”
Section: Resultssupporting
confidence: 79%
“…However, laboratory studies showing that P. digoneutis does not have a pre‐oviposition period (Haye et al , 2005) bring this assumption into question. Surveys conducted in 2007 and 2008 in south‐western Ontario, where P. digoneutis is now well established (Gariepy et al , 2008), showed that P. digoneutis adults were found in the field as early as 30 May, when Lygus nymphs were already present (Mason et al , 2009). However, parasitism of nymphs was not recorded before 13 June, suggesting that, under field conditions, P. digoneutis may not start to parasitize immediately after emergence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA from nymphs was extracted using an abbreviated chloroform: isoamyl alcohol protocol developed by Tilmon & Hoffmann [39]. DNA extractions along with negative controls were amplified using Peristenus species-specific primers as in [40]. Using this method, species-specific forward primers are combined with a genus-specific reverse primer to amplify a region including ITS1 and ITS2.…”
Section: (E) Parasitism Ratesmentioning
confidence: 99%